2019
DOI: 10.1016/j.tree.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Terrestrial Area of Habitat (AOH) and Its Utility for the IUCN Red List

Abstract: The International Union for Conservation of Nature (IUCN) Red List of Threatened Species includes assessment of extinction risk for 98 512 species, plus documentation of their range, habitat, elevation, and other factors. These range, habitat and elevation data can be matched with terrestrial land cover and elevation datasets to map the species' area of habitat (AOH; also known as extent of suitable habitat; ESH). This differs from the two spatial metrics used for assessing extinction risk in the IUCN Red List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
249
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(277 citation statements)
references
References 46 publications
1
249
0
2
Order By: Relevance
“…Using a dataset of 2,273 bird species in the Americas, 55% of all terrestrial birds found in the region, we have shown that our approach produced ranges that have reduced errors of omission, fewer errors of commission, and a higher accuracy when compared to expert-drawn alternatives. Thus, it also provides a more reliable, transparent, and consistent way to derive estimates of Area of Habitat (AOH), the newly recommended measure for the IUCN Red List (Brooks et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a dataset of 2,273 bird species in the Americas, 55% of all terrestrial birds found in the region, we have shown that our approach produced ranges that have reduced errors of omission, fewer errors of commission, and a higher accuracy when compared to expert-drawn alternatives. Thus, it also provides a more reliable, transparent, and consistent way to derive estimates of Area of Habitat (AOH), the newly recommended measure for the IUCN Red List (Brooks et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Draw the Extent of Occurrence (EOO) around presence points. The EOO is the upper bound of the distribution of a species (Brooks et al 2019) and should be mapped as the Minimum Convex Polygon (MCP) due to its consistency and scale-free properties (Joppa et al 2016; IUCN Red List Technical Working Group 2019; IUCN Standards and Petitions Committee 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the oft-overlooked caveats with global-scale assessments, such as data inaccuracy or inadequacy and broad generalization of inferences (Ocampo-Peñuela et al 2016; Norman & White 2019), our study demonstrates the utility of carefully designed large-scale investigations integrated with local knowledge and contexts. We present more nuanced distribution maps depicting species occurrences as probabilities within their Area of Habitat (Brooks et al 2019; Fig. S2), rather than Minimum Convex Polygons that over- or under-estimate species ranges (Ocampo-Peñuela et al 2016; Ramesh et al 2017).…”
Section: Discussionmentioning
confidence: 99%